2021
DOI: 10.1002/em.22454
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons induce endothelial injury through miR‐155 to promote atherosclerosis

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are considered as an external factor that induces atherosclerotic cardiovascular disease. Although miR‐155 is known to be involved in cardiovascular disease, whether it is involved in PAH‐induced arteriosclerosis remains unclear. We evaluated the effects of PAHs on vascularization, permeability, and miR‐155 expression in HUVECs. We found that PAHs‐induced sclerosis of HUVECs was characterized by increasing permeability, decreasing proliferation, and vascular lumen number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Inhalation of these materials induces local and systemic changes in the immune system which may impair critical cell defense mechanisms …..Our results demonstrated that exposure to PAHs leads to cell activation and deteriorates mitochondrial function of the macrophage thus facilitating growth of M. tuberculosis ." Sada-Ovalle et al (2018) respiratory tract; immune system; cell defense mechanisms; immune cells; macrophages; Mycobacterium tuberculosis ; THP-1; monocyte-derived macrophages; cell activation; mitochondrial function IIC “Polycyclic aromatic hydrocarbons induce endothelial injury through miR-155 to promote atherosclerosis" He et al (2021) atherosclerotic cardiovascular disease; miR-155; vascularization; permeability; miR-155 expression in HUVECs; permeability; proliferation; vascular lumen number; transcriptome sequencing; 63 genes; complement cascades; coagulation cascades; cytokine-cytokine receptor interaction; TNF signaling pathway; NF-kappa B signaling pathway; SERPIND1 DNS “this study suggests that exposure to PAHs leads to cortical thinning in the elderly in the absence of known neurological diseases. The affected brain regions included frontal, parietal, temporal, and insular lobes.…”
Section: Appendix 2cf Linkage Mechanisms and Biomarkersmentioning
confidence: 99%
“…Inhalation of these materials induces local and systemic changes in the immune system which may impair critical cell defense mechanisms …..Our results demonstrated that exposure to PAHs leads to cell activation and deteriorates mitochondrial function of the macrophage thus facilitating growth of M. tuberculosis ." Sada-Ovalle et al (2018) respiratory tract; immune system; cell defense mechanisms; immune cells; macrophages; Mycobacterium tuberculosis ; THP-1; monocyte-derived macrophages; cell activation; mitochondrial function IIC “Polycyclic aromatic hydrocarbons induce endothelial injury through miR-155 to promote atherosclerosis" He et al (2021) atherosclerotic cardiovascular disease; miR-155; vascularization; permeability; miR-155 expression in HUVECs; permeability; proliferation; vascular lumen number; transcriptome sequencing; 63 genes; complement cascades; coagulation cascades; cytokine-cytokine receptor interaction; TNF signaling pathway; NF-kappa B signaling pathway; SERPIND1 DNS “this study suggests that exposure to PAHs leads to cortical thinning in the elderly in the absence of known neurological diseases. The affected brain regions included frontal, parietal, temporal, and insular lobes.…”
Section: Appendix 2cf Linkage Mechanisms and Biomarkersmentioning
confidence: 99%